Comparison of open femoral exposure and percutaneous access in endovascular reconstruction of the thoracic aorta: a two-center retrospective study - D. P. Gaponov; T. N. Khafizov; K. V. Kochkina; I. I. Chernov; S. T. Enginoev; E. I. Shaposhnikova (Российский кардиологический журнал, 2022)
Aim. To analyze the efficacy and safety of the percutaneous transfemoral puncture technique for TEVAR (thoracis endovascular aortic repair).Material and methods. The retrospective study included 89 patients with aortic pathologies, for whom endovascular repair was performed: 51 patients (57%) with aortic dissection (type I DeBakey — 30 cases (58,8%) and type III — 21 (41,2%)), 38 (43%) patients with aortic aneurism. 82% of patients were male, the median age was 57 years (minimum age 17 years, maximum age 75 years). All patients were divided into two groups: in the first group (48 patients) endovascular aortic repair was performed under endotracheal anesthesia with open femoral exposure of the common femoral artery (CFA), in the second group (41 patients) — by percutaneous puncture method under local anesthesia. Technical and clinical aspects of procedures were analyzed.Results. Technical success of endovascular repair was achieved in 100% cases in both groups. The duration of the operation in the group with percutaneous access was statically significantly shorter (120 (94-150) minutes vs 87(60-120) minutes, p=0,001). Also, the time spent by patients in the intensive care unit and the period of hospitalization (18 (14-22) hours versus 1 (0-3) hours, p=0,001; 5 (4-6) days versus 4 (3-5) days, p=0,03) was shorter. In the open access group 2 (4,2%) patients developed access-related complications - acute thrombosis of the common femoral artery and hematoma of the postoperative wound, which required additional surgical aid - thrombectomy from the CFA, the second patient had evacuation of the hematoma of the postoperative wound. Cite-related complications in the second group were not observed. No major complications including neurological deficits and hospital mortality were observed in both groups.Conclusions. Thoracic endovascular aortic repair (TEVAR) using percutaneous access under local anesthesia in stable patients has proven to be safe and effective. The operation time is significantly reduced and this approach in most cases eliminates the need for the patient to stay in the intensive care unit in the early postoperative period. Possibility of early mobilization of the patient appears with reducing of the duration of hospitalization.